The Dialectical Imagination : a History of the Frankfurt School and the Institute of Social Research, 1923-1950 - Jay, Martin (Berkeley : University of California Press, 1996)
Herbert Marcuse, Erich Fromm, Max Horkheimer, Franz Neumann, Theodor Adorno, Leo Lowenthal--the impact of the Frankfurt School on the sociological, political, and cultural thought of the twentieth century has been profound. The Dialectical Imagination is a major history of this monumental cultural and intellectual enterprise during its early years in Germany and in the United States. Martin Jay has provided a substantial new preface for this edition, in which he reflects on the continuing relevance of the work of the Frankfurt School.
Cover Page; Title Page; Copyright Page; Dedication Page; Table of Contents; Preface to the 1996 Edition; Foreword; Introduction; Acknowledgments; 1. The Creation of the Institut fur Sozialforschung and Its First Frankfurt Years; 2. The Genesis of Critical Theory; 3. The Integration of Psychoanalysis; 4. The Institut's First Studies of Authority; 5. The Institut's Analysis of Nazism; 6. Aesthetic Theory and the Critique of Mass Culture; 7. The Empirical Work of the Institut in the 1940's; 8. Toward a Philosophy of History: The Critique of the Enlightenment; Epilogue; Chapter References.
Print version record.
Includes bibliographical references and index.
JSTOR
Keywords: Institut für Sozialforschung (Frankfurt am Main, Germany) -- History; Institut für Sozialforschung (Frankfurt am Main, Germany); Social sciences -- Research -- United States; Frankfurt school of sociology; Sciences sociales -- Recherche -- États-Unis.; École de Francfort (Sociologie); SOCIAL SCIENCE -- Methodology; SOCIAL SCIENCE -- Research; PHILOSOPHY -- Political; Frankfurt school of sociology; Social sciences -- Research; United States; critical theory; economics; education; erich fromm; european history; first world war; frankfurt school; franz neumann; german history; germany; hegel; herbert marcuse; intellectual history; late capitalism; leo lowenthal; marxism; max horkheimer; modern philosophy; modernism; nonfiction; philosophy; politics; second world war; social research; social theory; sociology; theodor adorno; united states; History